Tubuh sebagai Tanda: Tinjauan Literatur Sistematis tentang Penelitian Pantomim dalam Komunikasi Visual - Samsul Alam; Indar Sabri; Moh. Mujib Al Firdaus; Tri Haryotedjo; Deny Tri Aryanti (GETER : Jurnal Seni Drama, Tari dan Musik, 2026)
This study aims to synthesize contemporary pantomime scholarship by positioning the body as a primary sign system within the contexts of semiotics, embodiment, and visual dramaturgy. A Systematic Literature Review (SLR) guided by the PRISMA 2020 framework was conducted, analyzing 25 peer-reviewed articles published between 2010 and 2025. The findings identify five interconnected dimensions of pantomime performance: evolutionary communication, semiotic representation, embodied cognition, multimodal meaning-making, and visual dramaturgy. These dimensions highlight that pantomime extends beyond nonverbal communication by functioning as a performative system in which bodily action generates and organizes meaning. Based on this synthesis, the study proposes the Body as Sign Framework, which conceptualizes the body as a multidimensional system of signification operating across communicative, cognitive, semiotic, and performative processes. This framework offers an integrative theoretical model that connects previously fragmented perspectives in pantomime research. The study contributes to theatre and performance studies by providing a conceptual foundation for analyzing embodied meaning-making and body-based performance practices. It also offers directions for future research on visual dramaturgy and nonverbal communication in contemporary performance contexts.